Penggunaan Theory of Constraint dalam Penerapan Supply Chain Management (SCM) - Sabihaini, Sabihaini (Akutansi Bisnis & Manajemen ( ABM ), 2007)
Chain management focuses on integrating and managing the flow of good, service and information through the supply chain in order to make it responsive to customer needs while lowering total cost. Supply chain require close collaboration, cooperation, and communication among members to be effective. Supplier, and their customer must share information. It is the rapid flow of information among customers, suppliers, distributors, and producers that’s characterizes today’s supply chain management. Distorted information or the lack of information, such as inaccurate demand data or forecast. from the customer end can ripple back upstream through the supply chain and magnify demand variability at each stage, is know as the bullwhip effect.